2017
DOI: 10.1042/bcj20170258
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine methylation by DNMT2 facilitates stability and survival of HIV-1 RNA in the host cell during infection

Abstract: The enigmatic methyltransferase, DNMT2 (DNA methyltransferase 2), structurally resembles a DNA methyltransferase, but has been shown to be a tRNA methyltransferase targeting cytosine within a specific CpG in different tRNA molecules. We had previously shown that, during environmental stress conditions, DNMT2 is re-localized from the nucleus to the cytoplasmic stress granules (SGs) and is associated with RNA-processing proteins. In the present study, we show that DNMT2 binds and methylates various mRNA species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 45 publications
1
43
1
Order By: Relevance
“…Moreover, in mosquitoes ( Aedes aegypti ), the introduced endosymbiont, Wolbachia , suppressed expression of AaDnmt2 , but dengue virus (DENV) induced expression of AaDnmt2 and the authors concluded that AaDnmt2 plays an important role not only in the maintenance of Wolbachia infection in mosquito cells, but also in the resistance of mosquito cells to DENV infection [32] . Finally, it has been reported that cytosine methylation by DNMT2 promoted stability and survival of HIV-1 RNA in the host cell during infection [33] . As siRNA treatment resulted in elevated levels of beta-interferon in WI-38 and BJ cells (this study) and prolonged beta-interferon stimulation induced ROS-mediated DNA damage signaling and p53-dependent senescence in IMR90 human fibroblasts [34] , we decided then to analyze the effects of DNMT2 silencing on cell proliferation and longevity, intracellular redox equilibrium, genetic stability and epigenetic parameters.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, in mosquitoes ( Aedes aegypti ), the introduced endosymbiont, Wolbachia , suppressed expression of AaDnmt2 , but dengue virus (DENV) induced expression of AaDnmt2 and the authors concluded that AaDnmt2 plays an important role not only in the maintenance of Wolbachia infection in mosquito cells, but also in the resistance of mosquito cells to DENV infection [32] . Finally, it has been reported that cytosine methylation by DNMT2 promoted stability and survival of HIV-1 RNA in the host cell during infection [33] . As siRNA treatment resulted in elevated levels of beta-interferon in WI-38 and BJ cells (this study) and prolonged beta-interferon stimulation induced ROS-mediated DNA damage signaling and p53-dependent senescence in IMR90 human fibroblasts [34] , we decided then to analyze the effects of DNMT2 silencing on cell proliferation and longevity, intracellular redox equilibrium, genetic stability and epigenetic parameters.…”
Section: Discussionmentioning
confidence: 98%
“…In general, siRNA treatment, both control siRNA and DNMT2 siRNA, promoted an increase in the levels of beta-interferon in WI-38 and BJ cells (this study). More recently, the role of DNMT2 homologs during viral infections has been proposed in different biological model systems [31] , [32] , [33] . In Drosophila melanogaster , dDnmt2 has been reported to be required for innate immune responses and dDnmt2 mutant flies accumulated increasing levels of Drosophila C virus (DCV) and showed activated innate immune responses [31] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the HIV virus is able to increase its survival in the host cell using the RNA methylation activity of Dnmt2, increasing the stability of its own genome. Through infection, Dnmt2 relocates from the nucleus to the cytoplasmic stress granules and methylates the RNA virus, promoting the post-transcriptional stability of viral RNA [45]. RNAs interference (RNAi) have a strong association with different epigenetic mechanisms, such as histone methylation/acetylation and genomic DNA methylation [46].…”
Section: The Dnmt2 Gene Resides In the Arm Iil Of The D Willistoni Cmentioning
confidence: 99%
“…So far, only DNMT1, DNMT2, and DNMT3B have been implicated in HIV infection. 31,32 DNMT1, which is the most abundant DNMT in the cell and transcribed mostly during the S phase of the cell cycle, is primarily responsible for maintaining methylation through transfer of methyl groups to the hemimethylated DNA strands after DNA replication, but also has de novo DNMT activity. 33 In addition, DNMT1 influences transcriptional regulation by interacting with HDAC2 and novel corepressors to form a complex at replication foci.…”
Section: Dna Methyltransferasesmentioning
confidence: 99%
“…35 Recently, DNMT2 was shown to relocalize from the nucleus to stress granules and to methylate HIV-1 RNA in a sequence-independent manner, thereby providing posttranscriptional stability to the HIV-1 RNA. 32 DNMT3B, which is highly expressed in early embryonic stem (ES) cells, cannot differentiate between unmethylated and hemimethylated CpG sites, and cannot copy or contribute to the maintenance of a specific pattern of methylation. 33 However, DNMT3B has an important role in de novo methylation of unmodified cytosine residues.…”
Section: Dna Methyltransferasesmentioning
confidence: 99%